Managers and Students Playing Cournot: Experimental Evidence from Malaysia - Israel Waichman; Till Requate; Ch'ng Kean Siang (Kiel University, Department of Economics, 2008)
We report results from a Cournot triopoly experiment with different subject pools: German students, Malaysian students, and Malaysian managers. While German students play Nash, we reject the hypothesis that both Malaysian students and managers select the Nash quantity. Moreover, Malaysian managers perform significantly less competitively than Malaysian students. Finally, the affect of gender is opposite for German and Malaysian subjects.
Keywords: C72; C93; L13; D21; D43; 330; artefactual field experiment; subject pools; Cournot oligopoly; managers; non-cooperative behavior; Duopol; Oligopol; Nichtkooperatives Spiel; Experiment; Feldforschung; Studierende; Führungskräfte; Deutschland; Malaysia